1997
DOI: 10.1038/sj.bjp.0700889
|View full text |Cite
|
Sign up to set email alerts
|

Dose‐ and time‐dependence of l‐NAME neuroprotection in transient focal cerebral ischaemia in rats

Abstract: 1 In this study the e ect of the dose and administration time of N G -nitro-L-arginine methyl ester (L-NAME), an NO-synthase inhibitor, in a model of transient focal cerebral ischaemia in rats was investigated.2 Two injections of L-NAME were given, of 1, 3 and 10 mg kg 71 , 5 min and 3 h after the onset of ischaemia. None of the doses gave any striatal neuroprotection, but 1 and 3 mg kg 71 L-NAME reduced the infarcted volume in the cortex (by 26%, P50.01 for 1 mg kg 71 and 21%, P50.05 for 3 mg kg 71 ), whereas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0
4

Year Published

2000
2000
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(42 citation statements)
references
References 22 publications
2
36
0
4
Order By: Relevance
“…A possible mechanism by which neurotoxicity is induced is the formation of peroxynitrite anion (40,41). Thus, NOS inhibitors are considered to favor neuroprotection by inhibiting NO production, preventing neurotoxicity due to excess NO by scavenging oxygen-derived free radicals (41,42), which together may otherwise form peroxynitrite.…”
Section: Discussionmentioning
confidence: 99%
“…A possible mechanism by which neurotoxicity is induced is the formation of peroxynitrite anion (40,41). Thus, NOS inhibitors are considered to favor neuroprotection by inhibiting NO production, preventing neurotoxicity due to excess NO by scavenging oxygen-derived free radicals (41,42), which together may otherwise form peroxynitrite.…”
Section: Discussionmentioning
confidence: 99%
“…15 Possibly because of this dual action of NO, high doses of NOS inhibitors increase infarct size, whereas low doses are protective. 33 Inhibition of peroxynitrite formation is also feasible by suppressing superoxide levels. In parallel to our results, Asahi et al found a decrease in reperfusion-induced vascular injury and reduction in hemorrhagic complications when a free radical scavenger was administered at reperfusion.…”
Section: Discussionmentioning
confidence: 99%
“…As stated above, a non-selective NOS inhibitor, L-NAME (Figure 1a), can reduce the infarction volume, prevent the BBB breakdown and improve the recovery of neurological functions in cerebral ischemic mouse models [118,119] . However, L-NAME also targets eNOS, which has protective effects during the ischemic process.…”
Section: Nnos and Inos Inhibitorsmentioning
confidence: 99%